'Haciendas and Plantations': History and limitations of a 60-year-old taxonomy. (December 2018) - Edelman, Marc
In 1957, Eric R Wolf and Sidney W Mintz published 'Haciendas and Plantations in Middle America and the Antilles' in the Jamaican journal Social and Economic Studies . This article discusses the production of the Wolf and Mintz article, its analytical framework and the theoretical tensions it contains, and its subsequent influence, mainly though not exclusively on anthropological and historical scholarship about large landed properties in Latin America and the Caribbean. 'Haciendas and Plantations' appeared at a time when anthropologists such as Elman Service, Charles Wagley, and Marvin Harris were trying to make sense of agrarian Latin America by developing typologies of labour relations, rural populations, and forms of property. These efforts never successfully resolved the inherent tension between ethnographic or historical content, on the one hand, and Weberian ideal type definitions, on the other, although Wolf and Mintz's article came closer to doing this than the other works in the typological genre. In part, this was because it analysed discrete dimensions of large landed estates – capital, labour, land, markets, technology, sumptuary patterns, and so on – in a manner intended to stimulate cross-regional, cross-national, and trans-historical comparisons. 'Haciendas and Plantations', however, saw these elements as largely determining local-level outcomes on the ground and left little analytical room for contingency or rural class struggle in driving historical processes or shaping property relations and land use. Despite the article's scant historical content, it nonetheless continues to serve as a point of departure in early twenty-first-century agrarian studies and the analytical tensions it embodied are still significant in comparative social scientific research.